EVALUASI RTRW BERDASARKAN ASPEK RTH DAN KERENTANAN BENCANA (STUDI KASUS: KOTA MAGELANG) - Purwaningsih, Yuli; Setiawan, Heri; Wibowo, Adi (Universitas Muhammadiyah Gorontalo, 2024)
Evaluation of city planning based on aspects of Green Open Space (RTH) and disaster vulnerability is an important part of realizing a sustainable city. This research aims to evaluate the conformity of the Spatial Plan (RTRW) of Magelang City based on aspects of Green Open Space (RTH) and disaster vulnerability, as well as provide recommendations for the sustainability of the city in the future. The methods used include analysis of vegetation land cover using Random Forest classification and NDVI from Landsat 9 imagery in 2023 to evaluate RTH, as well as overlaying disaster vulnerability maps of floods and landslides from BNPB with the spatial plan map of RTRW. The results of the study indicate that the area of green open space in Magelang City still meets the minimum standard of 30% of the total area. However, there is a discrepancy in the use of the river border area of the Elo River covering an area of 1.14 hectares due to the presence of buildings standing on the river border. The areas of Wates and Gelangan Villages are prone to flood and landslide disasters with sloping conditions ranging from slightly steep to steep. The recommendations include the development of private green open spaces, drainage system management, not building houses around cliffs and rivers, socialization related to disasters, and emphasizing regulations to not build homes in river borders and not deforesting.